2022
DOI: 10.3390/vetsci9080411
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Blockade of the Renin-Angiotensin System Is Safe and Is a Potential Cancer Treatment for Cats

Abstract: The role of the renin-angiotensin system (RAS) in cancer growth and progression is well recognized in humans. However, studies on RAS inhibition with a single agent have not shown consistent anticancer effects, potentially due to the neoplastic cells utilizing alternative pathways for RAS activation. To achieve more complete RAS inhibition, multimodal therapy with several medications that simultaneously block multiple steps in the RAS has been developed for use in humans. In the present study, the safety of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…While this pilot study was not designed to assess whether the treatment had any impact on survival, the survival times reported in this study are similar to those reported for osteosarcoma and oral malignant melanoma in the literature [ 41 , 55 , 56 ]. In a similar study using multimodal blockade of the RAS as a treatment for squamous cell carcinoma in cats, it was noted that the oral and nasal planum neoplasms had unusually low mitotic rates for this type of cancer [ 38 ]. Unfortunately, in that study, the mitotic rate of the tumor prior to starting the trial was unknown, which, along with the small number of cats in the trial, made the interpretation of the mitotic rate results difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this pilot study was not designed to assess whether the treatment had any impact on survival, the survival times reported in this study are similar to those reported for osteosarcoma and oral malignant melanoma in the literature [ 41 , 55 , 56 ]. In a similar study using multimodal blockade of the RAS as a treatment for squamous cell carcinoma in cats, it was noted that the oral and nasal planum neoplasms had unusually low mitotic rates for this type of cancer [ 38 ]. Unfortunately, in that study, the mitotic rate of the tumor prior to starting the trial was unknown, which, along with the small number of cats in the trial, made the interpretation of the mitotic rate results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The multimodal blockade of the RAS has been assessed for safety in six cats [ 38 ]. In that study, cats with squamous cell carcinoma were treated for 8 weeks with the same medications as those used in the present study.…”
Section: Introductionmentioning
confidence: 99%